2009
DOI: 10.1002/mrm.21982
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of peristaltic and segmental motion in vivo in the rat small intestine using dynamic MRI

Abstract: Conventional methods of quantifying segmental and peristaltic motion in animal models are highly invasive; involving, for example, the external isolation of segments of the gastrointestinal (GI) tract either from dead or anesthetized animals. The present study was undertaken to determine the utility of MRI to quantitatively analyze these motions in the jejunum region of anesthetized rats (N ‫؍‬ 6) noninvasively. Dynamic images of the GI tract after oral gavage with a Gd contrast agent were acquired at a rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 40 publications
2
43
1
Order By: Relevance
“…Overall outlines of the exteriorised intestines are displayed below each ST map and each ST map is 20 min long (vertical axis). reduced after the administration of anaesthetic (Ailiani et al, 2009;Torjman et al, 2005), whereas, in pigs, the frequency of slow waves varied depending on the type of anaesthetic used (Tachecí et al, 2013). MS222, the general anaesthetic used in this study, has been shown to impair cardiovascular performance in fish (Hill et al, 2002;Houston et al, 1971).…”
Section: Research Articlementioning
confidence: 76%
See 1 more Smart Citation
“…Overall outlines of the exteriorised intestines are displayed below each ST map and each ST map is 20 min long (vertical axis). reduced after the administration of anaesthetic (Ailiani et al, 2009;Torjman et al, 2005), whereas, in pigs, the frequency of slow waves varied depending on the type of anaesthetic used (Tachecí et al, 2013). MS222, the general anaesthetic used in this study, has been shown to impair cardiovascular performance in fish (Hill et al, 2002;Houston et al, 1971).…”
Section: Research Articlementioning
confidence: 76%
“…Often, different patterns dominate in different regions of the gut, but this may also depend on the fed state of the animal (Ailiani et al, 2009;Berthoud et al, 2002;Bogeski et al, 2005;Chen et al, 2013;D'Antona et al, 2001;Ferens et al, 2005;Hennig et al, 1997;Hennig et al, 1999;Hennig et al, 2010). Mixing and propulsion can be achieved by either non-propagating (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This motility is generally characterised by an initial and slight increase in organ diameter, followed by a contraction to approximately 75% its initial diameter, a lag phase, and a slow increase back to its original size. This general description of a segmental contraction has been observed in the canine (Bayliss and Starling, 1899), in the ileum of a cat (Krishnan, 1932), in the rat jejunum (Ailiani et al, 2009), and in the guinea pig jejunum (Gwynne and Bornstein, 2007), to name a few. Of note, is the observation that the compression phase is significantly more rapid than the relaxing phase.…”
Section: Longitudinal Contractionmentioning
confidence: 85%
“…See, for example, Ailiani et al (2009) and Thuneberg and Peters (2001). Here we model the simple situation where two segmental contractions occur with the same contraction depth and phase, at a distance d from one another.…”
Section: Doublementioning
confidence: 99%
See 1 more Smart Citation